effect of some adenosine compounds on smooth muscles of the sheep bladder osteius ovis L - AL-Ani, fakher S.; Mahmood, sade. M.; AL-Ani, iqbal N. (Journal of the Faculty of Medicine Baghdad, 2005)
Background: